1994
DOI: 10.1017/s0950268800057770
|View full text |Cite
|
Sign up to set email alerts
|

Host–microflora interaction in Systemic Lupus Erythematosus (SLE): colonization resistance of the indigenous bacteria of the intestinal tract

Abstract: SUMMARYExperimental data suggest a role for the microflora in Systemic Lupus Erythematosus (SLE). Anti-ds-DNA antibodies may be pathogenic in SLE by forming immune complexes with DNA. Foreign bacteria in the intestines could constitute the stimulus for anti-ds-DNA antibody production in SLE. Colonization Resistance (CR) is the defence capacity of the indigenous microflora against colonization of the intestines by foreign bacteria. A low CR implies increase of translocation of bacteria and a higher chance of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Flares of lupus often occur in association with infection and there is evidence that patients with lupus have abnormalities in the clearance of bacteria and other pathogens suggesting a possible role of microbial antigens in inducing disease activity (26). Furthermore, bacterial DNA has been isolated from the serum of lupus patients with clinically active disease in the absence of known infection, while infection with the BK virus is associated with anti-DNA production in both man and animal models (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Flares of lupus often occur in association with infection and there is evidence that patients with lupus have abnormalities in the clearance of bacteria and other pathogens suggesting a possible role of microbial antigens in inducing disease activity (26). Furthermore, bacterial DNA has been isolated from the serum of lupus patients with clinically active disease in the absence of known infection, while infection with the BK virus is associated with anti-DNA production in both man and animal models (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…This evidence supports the determining role of intestinal microbiome in promoting development and activity flare of lupus in SNF1 mice. In SLE patients, gut dysbiosis was first observed many years ago by Apperloo-Renkema et al [53], who demonstrated the presence of different biotypes of Enterobacteriaceae in active SLE than inactive patients and healthy subjects. Recently, Hevia et al [54] found a lower Firmicutes/Bacteroidetes ratio in SLE patients than in healthy subjects (median ratio 1.97 vs. 4.86; p < 0.002) and demonstrated that microbiota isolated from SLE patient stool samples was able to promote Th17 differentiation from naïve CD4-positive lymphocytes more than healthy control microbiota.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 98%
“…Colonization resistance was found to be lower in active SL patients than in healthy individuals (P = 0.09, Wilcoxon one sided, with correction for ties) suggesting that in patients with SL, various types and more bacteria are translocating across the gut wall than in healthy individuals, due to lower colonization resistances in these patients. Some of these may serve as polyclonal B cell activators or as antigens cross-reacting with DNA [183]. Thus, administering probiotic bacteria such as bifidobacteria which may restore normal gutmicroflora and reduce the inflammatory response and production of such antibodies should be beneficial.…”
Section: Lupus and Probioticsmentioning
confidence: 99%